Selective and Sequential Extraction of Lead in Soil Samples and Plant Parts Taken from a Serpentine and Copper Mining Area - Kaplan, Olcay; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2009)
Speciation is important to determine the mobility, bioavailability and/or toxicity of trace elements in soils because the total concentrations of metals are not adequate for determination of these properties. In this study, selective and four stage sequential extraction procedures were used to determine different Pb phases in soil samples. Soil samples and plants grown in these soils were collectcd from a serpentine and copper-mining area in Maden-Elazig-Turkey. The extracted fractions were: exchangeable/carbonate, reducible-iron/manganese oxides, and oxidizable-organic matter and sulfides, and residual except silicates. Pb concentrations in soil and plant samples were determined by flame atomic absorption spectrometry (FAAS) and inductively coupled plasma- mass spectrometry (ICP-MS). Higher Pb concentrations in the EDTA and NH2OHHCl extracts were found in most of the Studied soils, compared to other extracts. Therefore, it can be concluded that Pb concentrations in potentially mobile phases are considerable. Because of a translocation factor higher than I for Brassicasea plant, Brassicasea leaves can be considered as a hyperaccumulator plant for lead.
Keywords: Trace-Metals; Speciation; Fruits; Cadmium; Nickel; Turkey; Health; Keban